Pengembangan Perumahan Berbasis Syariah dan Permasalahannya di Propinsi Jambi - Supeno Supeno; M Ansori (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
This study aims to determine the concepts and patterns developed by sharia-based housing developers in Jambi Province and detect problems faced, the research uses empirical research types by directly interviewing the development company directors and marketing department, the research results can be obtained that the concept used by sharia-based housing developers is the concept of free from usury transactions and free from tyranny in the form of free from late fines and free from confiscation by conventional banks, the developed pattern can be in the form of direct purchases to developers or Islamic banks to buy houses to developers in cash then banks Sharia sells it to consumers on credit. Hamabtan faced by the developers is the low level of public understanding of the concept of sharia-based housing and the existence of practices that hinder the licensing process carried out by certain elements. There is a need for the participation of local governments to participate in campaigning for usury-free communities and to supervise and strictly process the licensing of sharia-based housing development from unscrupulous acts.